The Analysis of thermal efficiency in Star Energy Gothermal Darajat - Pratama, Muhammad Pashya Rifky; Utomo, Teguh; Wibawa, Unggul (Faculty of Engineering, Universitas Brawijaya, 2023)
After years of operation, the plant will no longer operate optimally according to its design. The practice of the work cycle shows that the original value of thermal efficiency will always be below 100%, this is because during the cycle process of creating work, the energy received by the system by heat transfer will not be fully received and will be absorbed by the environment. In this research, thermal efficiency analysis was carried out in accordance with the first and second laws of thermodynamic efficiency and thermoeconomic calculations to calculate losses. Based on calculations that have been carried out, the thermal efficiency of the Star Energy Geothermal Darajat unit-3 geothermal power plant system is 21.72% with the largest exergy loss being in the condenser component of 62,219,418 kW with an exergy loss cost of 252,766,682.24 Rp/ days and the smallest is in the cooling tower of 599,362 kW with exergy loss costs of 23,655,907.11. Rp/day from the following results it can be seen that this efficiency value depends on the performance of each component.